Acceptorless dehydrogenative coupling with Ru-based catalysts for the synthesis of N-heteroaromatic compounds. Issue 44 (27th October 2020) - Zhang, Jing; Guo, Bin; Young, David James; Li, Hong-Xi
Abstract : A summary of recently developed ruthenium catalysts for the synthesis of N-heteroaromatic compounds via acceptorless dehydrogenative coupling (ADC) and the related auto-transfer-hydrogenative (ATH) reaction. Abstract : Ru-Catalyzed acceptorless dehydrogenative coupling (ADC) and auto-transfer-hydrogenative (ATH) reactions are effective, versatile transformations for the constructions of N -heteroaromatic compounds from alcohols. Water and hydrogen are the by-products and the starting alcohols are less toxic, more readily available and more easily handled than their halogenated counterparts. A variety of homogeneous ruthenium catalysts, alcohols and partner-substrates such as amines, ammonia, amidines and nitriles, have been used to build N -heteroaromatic compounds in one-pot, multi-step syntheses. This review details recently reported Ru catalysts employed for these reactions, describing the scope of each methodology, proposed reaction mechanisms, regioselectivity of coupling and applications in synthesis.